Regimes of Mobility Across the Globe. - Glick Schiller, Nina; Salazar, NoelB. (Journal of Ethnic & Migration Studies, 2013)
Mobility studies emerged from a postmodern moment in which global ‘flows’ of capital, people and objects were increasingly noted and celebrated. Within this new scholarship, categories of migrancy are all seen through the same analytical lens. This article andRegimes of Mobility: Imaginaries and Relationalities of Power, the special issue ofJEMSit introduces, build on, as well as critique, past and present studies of mobility. In so doing, this issue challenges conceptual orientations built on binaries of difference that have impeded analyses of the interrelationship between mobility and stasis. These include methodological nationalism, which counterpoises concepts of internal and international movement and native and foreigner, and consequently normalises stasis. Instead, the issue offers a regimes of mobility framework that addresses the relationships between mobility and immobility, localisation and transnational connection, experiences and imaginaries of migration, and rootedness and cosmopolitan openness. The introduction highlights how, within this framework and its emphasis on social fields of differential power, the contributors to this collection ethnographically explore the disparities, inequalities, racialised representations and national mythscapes that facilitate and legitimate differential mobility and fixity. Although the authors examine nation-state building processes, their analysis is not confined by national boundaries.